2016
DOI: 10.4103/0253-7613.178825
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, comparative, open-label study of efficacy and tolerability of alfuzosin, tamsulosin and silodosin in benign prostatic hyperplasia

Abstract: Objectives:Benign prostatic hyperplasia (BPH) is a common and progressive disease affecting elderly males, often associated with lower urinary tract symptoms (LUTS). α1-blockers are the mainstay in symptomatic therapy of BPH. Because of their greater uroselectivity and minimal hemodynamic effects, alfuzosin, tamsulosin, and silodosin are generally preferred. The aim of this study was to compare the efficacy and tolerability of alfuzosin, tamsulosin, and silodosin in patients with BPH and LUTS.Methods:Ninety su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 15 publications
4
17
0
2
Order By: Relevance
“…2 Early onset of improvement in I-PSS has been reported for silodosin treated patients within 3-4 days, 14 days and 4 weeks respectively by many studies. 16,17,20 Similarly, an early and significant onset of improvement in I-PSS in alfuzosin treated patients has been observed Saad F et al 19 In the present study significant and comparable improvement was observed on the QoL due to urinary symptoms in both the treatment groups (p <0.001).…”
Section: Qolsupporting
confidence: 79%
See 1 more Smart Citation
“…2 Early onset of improvement in I-PSS has been reported for silodosin treated patients within 3-4 days, 14 days and 4 weeks respectively by many studies. 16,17,20 Similarly, an early and significant onset of improvement in I-PSS in alfuzosin treated patients has been observed Saad F et al 19 In the present study significant and comparable improvement was observed on the QoL due to urinary symptoms in both the treatment groups (p <0.001).…”
Section: Qolsupporting
confidence: 79%
“…Decline in I-PSS with silodosin has been reported by various studies. 2,[15][16][17] In the present study, for SD combination mean change in I-PSS from baseline was (-7.15) at 12 weeks. A similar decrease (-8.3) and (-6.4) in mean I-PSS from baseline with silodosin was reported by many 12-week studies.…”
Section: Qolsupporting
confidence: 41%
“…Ten trials randomized men with LUTS attributed to BPH ( n = 1799) to silodosin 8 mg daily versus tamsulosin 0.2–0.4 mg daily [1322]. Table 1 provides baseline characteristics.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Table 1 provides baseline characteristics. Overall, the RoB was low in two trials [13,18], moderate in six trials [1416,2022], and high in two trials [17,19]. …”
Section: Evidence Synthesismentioning
confidence: 99%
“…IPSS was used to assess the severity of LUTS as described elsewhere. 10 IPSS was assessed at baseline and at the follow up visits after 2, 4, 8 and 12 weeks of treatment initiation by the investigator. The patients were instructed to carefully observe the severity of their urinary complaints and report the same when asked about it at the subsequent visit during the recording of the IPSS.…”
Section: Methodsmentioning
confidence: 99%